Perceived Severity as a Potential Mediator in Estimation of Disease Frequencies Felicia Trembath - Trembath, Felicia (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2018)
A heuristic is a mental strategy for making judgments quickly and efficiently. The recognition heuristic was first described by Goldstein and Gigerenzer in 2002 (Goldstein & Gigerenzer, 2002), and holds that when an individual is asked to choose between two objects and they only recognize one of the two objects, that they will choose the recognized object. This concept has been tested in a variety of situations from asking individuals to choose the city with the largest population size to having them choose who will win a rugby match. In most instances individuals adhere to the recognition heuristic about 90% of the time (Goldstein & Gigerenzer, 2002). That is to say in situations where an individual recognizes only one of the choices presented, 90% of the time they will select the recognized item. Individuals are more likely to select the recognized item when under a time constraint to make a decision (Pachur & Hertwig, 2006). However, a strange phenomenon has been demonstrated when individuals are asked to estimate frequencies of diseases. When participants are asked to estimate rates of disease frequencies, the adherence rate to the recognition heuristic drops to 62% (Pachur & Hertwig, 2006). According to the principle of the recognition heuristic, it is applied when one item is recognized and the other is not. However, when asked to estimate frequencies of diseases, 38% of the time participants recognize only one of the diseases, yet they chose not to use the recognition heuristic. The lower adherence rate in the case of estimation of disease frequencies is a puzzling phenomenon and suggests that participants may be considering other information instead of, or in addition to recognition. Perhaps in estimations of city populations in foreign countries, the only information that is known is that the individual has heard the name of one of the cities in the media, thus the recognition heuristic is followed 90% of the time (Goldstein & Gigerenzer, 2002). On the other hand, individuals have ideas and opinions about diseases. In fact, they or a close member of their social network may have even been afflicted by the disease in question. This situation thus poses one where an individual has pre-existing notions about diseases and may rely upon these notions rather than recognition alone in formulating estimates of disease frequencies. In the inception of the recognition heuristic, Goldstein and Gigerenzer (2002) postulated that “no other information about the unrecognized object is searched for and therefore, no other information can reverse the choice determined by recognition (p. 82).” Yet the discrepancy in adherence to the recognition heuristic in the case of estimating disease frequencies calls into question whether in some situations individuals are in fact searching for and considering other information (Bröder & Eichler, 2006; Oppenheimer, 2003; Pachur & Hertwig, 2006). It stands to reason that if no information is known about an object, that no information about that object can be considered when making an estimation of frequency. However, when testing the recognition heuristic, researchers merely measure whether or not a person selects the recognized object, any other information that an individual knows or perceives about the two choices remains unmeasured. Thus there is an unidentified amount of information known about the recognized choice, which could be considered by the individual making a selection. In the case of estimation of disease frequencies, the unidentified knowledge is likely the individual’s perceived severity of that disease. This article proposes that when estimating disease frequencies the application of the recognition heuristic is mediated by perceived disease severity, and further describes the plausible mechanism by which that meditation may occur.